1999
DOI: 10.1128/aac.43.6.1401
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal Activity of Nikkomycin Z in Combination with Fluconazole or Itraconazole

Abstract: Nikkomycins are nucleoside-peptide antibiotics produced byStreptomyces species with antifungal activities through the inhibition of chitin synthesis. We investigated the antifungal activities of nikkomycin Z alone and in combination with fluconazole and itraconazole. Checkerboard synergy studies were carried out by a macrobroth dilution procedure with RPMI 1640 medium at pH 6.0. At least 10 strains of the following fungi were tested: Candida albicans, other Candida spp., Cryptococcus neoformans, Coccidioides i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(71 citation statements)
references
References 30 publications
1
69
0
Order By: Relevance
“…However, these results must be interpreted with caution because recently the criteria for evaluating interactions have changed and FICI values over 0.5 are now considered to be indicative of no synergy [123]. Li and Rinaldi [124] demonstrated that the combination of the nucleoside-peptide antibiotic nikkomycin Z, which is a chitin synthase inhibitor, with ITC resulted in moderate in vitro growth inhibition of Scedosporium spp. The combination AMB/micafungin (MFG) shows in vitro synergistic effect against S. apiospermum [125].…”
Section: In Vitro Antifungal Susceptibilitymentioning
confidence: 96%
“…However, these results must be interpreted with caution because recently the criteria for evaluating interactions have changed and FICI values over 0.5 are now considered to be indicative of no synergy [123]. Li and Rinaldi [124] demonstrated that the combination of the nucleoside-peptide antibiotic nikkomycin Z, which is a chitin synthase inhibitor, with ITC resulted in moderate in vitro growth inhibition of Scedosporium spp. The combination AMB/micafungin (MFG) shows in vitro synergistic effect against S. apiospermum [125].…”
Section: In Vitro Antifungal Susceptibilitymentioning
confidence: 96%
“…The naturally occurring nikkomycins are nucleoside-peptide antibiotics that inhibit the synthesis of cell wall chitin, a polysaccharide found in most fungi but not in mammalian cells, as competitive analogues of the substrate UDP-N-acetylglucosamine for the enzyme chitin synthase [14,27]. The effect is analogous to the action of the b-lactam antibiotics on bacteria cell walls, leading to osmotic lysis [28]. Nikkomycins were first described as a class of drugs in 1976, isolated as a result of a program to discover fungicides for agricultural use [29].…”
Section: Overview Of Antifungal Classesmentioning
confidence: 97%
“…Nikkomycins were first described as a class of drugs in 1976, isolated as a result of a program to discover fungicides for agricultural use [29]. The antifungal activity of nikkomycin Z against opportunistic fungi has been reportedly low in many experimental fungal models, including ineffective growth inhibition against Aspergillus fumigatus [28,[30][31][32], leaving combination therapy as a potential option.…”
Section: Overview Of Antifungal Classesmentioning
confidence: 99%
“…Synergic activity of various compounds against fungi has been reported by many workers [9]. Theoretically, the simultaneous administration of polyenes and imidazoles should result in antagonism because these drugs exert their action either directly on ergosterol or enzymes involved in its synthesis.…”
Section: Introductionmentioning
confidence: 98%